Budaya Sebagai Pusaka Bangsa Indonesia - Rico Mulyawan; Dinie Anggraeni Dewi (International Forum of Researchers and Lecturers, 2024)
Culture is a result of human creativity, taste, intention which is passed down from generation to generation. Culture is not just dance, clothing, houses, customs, or songs, but culture is a complex system which is full of physical and spiritual values ​​that strengthen the soul. A strong soul will not be easily swayed by any attack. A strong soul will be able to live by combining the progress of the times with noble values. Using qualitative methods such as literature studies, here we will discuss culture and globalization. This aims to ensure that each of us can be more inspired by God's grace towards all of us, in which God has made us part of the great, noble, civilized Indonesian nation to become leaders on earth.